2013
DOI: 10.1186/1748-717x-8-166
|View full text |Cite
|
Sign up to set email alerts
|

Palliative radiotherapy in patients with a poor performance status: the palliative effect is correlated with prolongation of the survival time

Abstract: BackgroundThe purpose of this study was to analyze the efficacy and tolerability of palliative radiotherapy (RT) in patients with a poor performance status (PS) and to evaluate the relationship between the palliative effect and survival time.MethodsOne hundred and thirty-three patients with a poor PS (Eastern Cooperative Oncology Group 3 or 4) were treated with palliative RT using the three-dimensional conformal technique and retrospectively analyzed. Each patient's primary symptom treated with palliative RT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Although measures of a palliative effect are more meaningful when evaluating a palliative treatment, they are more prone to bias and difficult to assess retrospectively. However, in humans treated with palliative radiotherapy, palliation is directly correlated with survival time . This is also likely true in veterinary patients, where euthanasia decisions are based heavily on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although measures of a palliative effect are more meaningful when evaluating a palliative treatment, they are more prone to bias and difficult to assess retrospectively. However, in humans treated with palliative radiotherapy, palliation is directly correlated with survival time . This is also likely true in veterinary patients, where euthanasia decisions are based heavily on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study found that the use of palliative TRT in stage IV NSCLC was associated with younger patients, the receipt of chemotherapy, and having undergone surgery of metastatic sites, which indicates that the survival benefits of palliative TRT may be due to confounding factors . Controlling the primary tumor was found to prolong patient survival and may lead to long‐term survival of patients with stage IV NSCLC . Refusing palliative RT led to poor survival .…”
Section: Discussionmentioning
confidence: 99%
“…33 Controlling the primary tumor was found to prolong patient survival and may lead to long-term survival of patients with stage IV NSCLC. 34,35 Refusing palliative RT led to poor survival. 36 Both the 2011 American Society for Radiation Oncology (ASTRO) Guideline and the 2014 European Society for Medical Oncology (ESMO) Guideline concluded that RT plays a major role in controlling the symptoms of metastases, such as painful chest wall disease, superior vena cava syndrome, soft tissue, or neural invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Phase III study results indicate that postoperative full-dose EBRT reirradiation combined with chemotherapy after salvage surgery significantly improved disease free survival, but had no significant impact on overall survival. Regarding toxicity, an increase in both acute and late toxicity was observed [ 147 ]. The palliative effect of a given treatment is strongly correlated with the prolongation of the survival time, and may contribute to improving the remaining survival time in patients with metastatic/advanced cancer with a poor performance status [ 148 ].…”
Section: Palliative Treatmentsmentioning
confidence: 99%